Transforming Religious Character Development to Prevent Bullying Among Santri: A Case Study of an Indonesian Islamic Boarding School - Moch Jauharul Maknun Al Ma’ie; Jazilur Rahman (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Bullying remains a persistent challenge in educational institutions, including Islamic boarding schools, where religious values are expected to foster respectful and harmonious social relationships. This study aimed to examine how the transformation of religious character development contributes to bullying prevention among santri at an Indonesian Islamic boarding school. Employing a qualitative case study design, the research was conducted at Pondok Pesantren Nurul Jadid, East Java, Indonesia, from January to May 2026. Data were collected through semi-structured interviews, participant observation, and document analysis involving six purposively selected participants representing institutional leaders, counselors, mentors, and students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while the interpretation was guided by Thomas Lickona’s character education framework. The findings reveal that bullying prevention is achieved through the transformation of religious character development into an integrated educational system comprising four interconnected pillars: the Santri Trilogy as the foundation of moral understanding (moral knowing), intensive mentoring through the wali asuh program and Furudhul Ainiyah Akhlak reinforcement to cultivate emotional awareness (moral feeling), continuous religious habituation and counseling to promote prosocial behavior (moral action), and restorative educational sanctions that reinforce an anti-bullying culture. These findings demonstrate that sustainable bullying prevention depends on the systematic internalization of religious values through institutional culture rather than punitive disciplinary approaches alone. The proposed model contributes to the advancement of Islamic character education and offers practical guidance for developing safer, more inclusive, and value-based educational environments in Islamic boarding schools.